Augmented Reality in Engineering Education: An Application for Electronic Circuits Laboratory - Iriqat, Sanaa; Vatansever, Fahri (Computer animation and virtual worlds, 2025)
ABSTRACT Engineering education faces challenges in effectively conveying complex theoretical knowledge and practical skills. Traditional teaching tools like smart boards, education kits, web pages, and computer‐based simulators often fall short in bridging the gap between theory and hands‐on application. Augmented reality (AR) has emerged as a promising solution to fill this educational gap by providing immersive and interactive learning experiences. In this study, an AR‐based application has been developed for operational amplifiers. Agile methodology and the ADDIE learning development model were used in the system development and instructional design of this application. This application, which requires only a smartphone and a breadboard, detects the circuit marker when users point their smartphone camera at it. After detection, the user can interact with the interface to choose whether the system shows input–output signals for different component values, the output voltage formula, a 3D model, or a brief lecture about the used amplifier. These virtual elements are overlaid onto the real‐world breadboard based on the user's selection. This integration of AR technology provides an immersive, interactive learning experience, allowing students to visualize and interact with circuit elements in real time.